Applications of density functional theory to biological and bioinorganic chemistry - Mingos, D. Michael P.; Putz, Mihai V. (Structure and Bonding, 2013)
Dennis R. Salahub et al.          Recent Progress in Density Functional Methodology for Biomolecular Modeling Eugene Serge Kryachko          Density Functional Theory and Molecular Interactions: Dispersion Interactions Radu Silaghi-Dumitrescu        Redox Activation of Small Molecules at Biological Metal Centers Mauro Causà et al.     The Bond Analysis Techniques (ELF and Maximum Probability Domains) to a Family of Models Relevant to Bio-Inorganic Chemistry Arindam Chakraborty et al.        Biological Activity and Toxicity: A Conceptual DFT Approach Mihai V. Putz and Ana-Maria Putz     DFT Chemical Reactivity Driven by Biological Activity: Applications for the Toxicological Fate of Chlorinated PAHs